The global burden of type 2 diabetes attributable to high body mass index in 204 countries and territories, 1990–2019: An analysis of the Global Burden of Disease Study - Zhang, Xuexue; Wang, Xujie; Wang, Miaoran; Hu, Biaoyan; Tang, Wei; Wu, Yufei; Gu, Jiyu; Ni, Tian; Li, Qiuyan (Frontiers in Public Health, 2022)
Background: High body mass index (BMI) plays a critical role in the initiation and development of type 2 diabetes (T2D). Up to now, far too little attention has been paid to the global burden of T2D attributable to high BMI. This present study aims to report the deaths and disability-adjusted-life-years (DALYs) of T2D due to high BMI in 204 countries and territories from 1990 to 2019. Methods: Data on T2D burden attributable to high BMI were retrieved from the Global Burden of Diseases, Injuries, and Risk Factors study (GBD) 2019. The global cases, age-standardized rates of mortality (ASMR) and disability-adjusted life years (ASDR) attributable to high BMI were estimated by age, sex, geographical location, and socio-demographic index (SDI). The estimated annual percentage change (EAPC) was calculated to quantify the trends of ASMR and ASDR during the period 1990-2019. Results: Globally, there were 619494.8 deaths and 34422224.8 DALYs of T2D attributed to high BMI in 2019, more than triple in 1990. Moreover, the pace of increase in ASMR and ASDR had accelerated during the 1990–2019 time period, with EAPC of 1.36 (95% CI: 1.27, 1.45) and 2.13 (95% CI: 2.1-2.17), especially in males, South Asia, and low-middle-SDI regions. Oceania was the high-risk areas of standardized T2D deaths and DALYs attributable to high BMI in 2019, among which Fiji was the country with the heaviest burden. In terms of SDI, middle SDI regions had the biggest T2D-related ASMR and ASDR in 2019. Both number and age-standardized rate in death and DALYs were lower in females than in males in age groups < 60 years, whereas higher in females than in males in age groups ≥ 60 years globally. Conclusion: The globally deaths and DALYs of T2D attributable to high BMI are substantially increased from 1990 to 2019. High BMI as a major public health problem need to be tackled properly and timely in T2D.